2010
DOI: 10.1002/stem.467
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition-Derived Cells Exhibit Multilineage Differentiation Potential Similar to Mesenchymal Stem Cells  

Abstract: Summary The epithelial-to-mesenchymal transition (EMT) is an embryonic process that becomes latent in most normal adult tissues. Recently, we have shown that induction of EMT endows breast epithelial cells with stem cell traits. In this report, we have further characterized the EMT-derived cells and shown that these cells are similar to mesenchymal stem cells (MSCs) with the capacity to differentiate into multiple tissue lineages. For this purpose, we induced EMT by ectopic expression of Twist, Snail or TGF-β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(190 citation statements)
references
References 46 publications
9
179
1
1
Order By: Relevance
“…The identification of GD2 as a marker for breast CSCs is based on our recent work linking EMT-derived breast epithelial cells with bone marrow-derived multipotent MSCs (13). In support of this notion, Weissman's group recently demonstrated that CD271, another bone marrow-derived MSC marker, is also highly expressed on melanoma-initiating cells (28), suggesting that a number of cell surface markers expressed on MSCs may also be shared by CSCs from different tumor types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of GD2 as a marker for breast CSCs is based on our recent work linking EMT-derived breast epithelial cells with bone marrow-derived multipotent MSCs (13). In support of this notion, Weissman's group recently demonstrated that CD271, another bone marrow-derived MSC marker, is also highly expressed on melanoma-initiating cells (28), suggesting that a number of cell surface markers expressed on MSCs may also be shared by CSCs from different tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that, following the induction of EMT, human mammary epithelial cells show functional properties similar to those of human bone marrowderived MSCs (13). Therefore, we hypothesized that the cell markers expressed on the surface of MSCs could also be expressed on the surface of breast CSCs.…”
Section: Gd2 Enriches For Breast Cscsmentioning
confidence: 95%
See 2 more Smart Citations
“…Yin et al (2010) reported that Twist1 may be an important regulator of stemness in epithelial ovarian cancer cells. The EMT-derived cells, which are induced by Twist1 in human mammary epithelial cells, exhibited the potential for multilineage differentiation similar to mesenchymal stem cells (Battula et al, 2010). Twist2, similar to Twist1, is a potential mediator of mesenchymal stem cell self-renewal and lineage commitment.…”
Section: Cdk2àap1mentioning
confidence: 98%